ENHANCING THE RHEOLOGICAL PROPERTIES OF OIL-BASED MUD THROUGH THE INCORPORATION OF POTATO STARCH - Abdul Gafar Karim; Aprilino Alfa Kurmasela; Muhammad Rizqie; Dody Finansa; Aditya Rizky (Sekolah Tinggi Teknologi MIGAS, 2023)
Oil-based drilling muds are effective in protecting formation integrity and resisting high temperatures, but additives are necessary to optimize their performance. This study proposes using potato starch as an additive to improve the performance of oil-based drilling mud. Potato starch was chosen because of its ability to act as a viscosifier or thickener that remains unaffected by water salinity. The research involved adding different concentrations of potato starch to a fresh oil-based drilling mud, with two Oil-to-Water Ratio (OWR) ratios, 75:25 and 80:20, employed for the two trials. Rheological testing was utilized to assess the influence of potato starch additives on the viscosity, gel strength, plastic viscosity, and yield point of drilling mud. The findings showed that the incorporation of potato starch in oil-based drilling mud can enhance its rheological values. Using potato starch as an additive offers the potential to tackle wells that have formation conditions that are brittle and sensitive to water and high temperatures. This research provides novel insights into the development of more effective and eco-friendly drilling mud formulations.